The effect of endometriosis on in vitro fertilisation outcome: a systematic review and meta‐analysis. Issue 11 (3rd July 2013) - Harb, HM; Gallos, ID; Chu, J; Harb, M; Coomarasamy, A
<x xml:space="preserve">Abstract</x> Background Endometriosis is found in 0.5–5% of fertile women and 25–40% of infertile women. It is known that endometriosis is associated with infertility, but there is uncertainty whether women with endometriosis have adverse pregnancy outcomes in in vitro fertilisation (IVF) treatment. Objectives To explore the association between endometriosis and IVF outcome. Search strategy Searches were conducted on MEDLINE, EMBASE, Cochrane Library and Web of Science (inception, December 2012) in all languages, together with reference lists of retrieved papers. Selection criteria Studies comparing IVF outcome in women with endometriosis with women without endometriosis. Patients were classified by stage of endometriosis. The outcomes were fertilisation, implantation, clinical pregnancy and live birth rates. Study selection was conducted independently by two reviewers. The Newcastle‐Ottawa Quality Assessment Scale was used for quality assessment. Data collection and analysis Data extraction was conducted independently by two reviewers. Relative risks from individual studies were meta‐analysed. Main results Twenty‐seven observational studies were included, comprising 8984 women. Meta‐analysis of these studies showed that fertilisation rates were reduced in stage I/II of endometriosis (relative risk [RR] = 0.93, 95% confidence interval [95% CI] 0.87–0.99, P = 0.03). There was a decrease in the implantation rate (RR = 0.79, 95% CI 0.67–0.93, P = 0.006) and clinical pregnancy rate (RR = 0.79, 95% CI 0.69–0.91, P = 0.0008) in women with stage III/IV endometriosis undergoing IVF treatment. Conclusion The presence of severe endometriosis (stage III/IV) is associated with poor implantation and clinical pregnancy rates in women undergoing IVF treatment.